The Relationship between Social Support, Academic Motivation with Academic Self-Efficacy of High School Students - peyman yarmohammadzadeh; zahra Feizollahi (جامعه شناسی کاربردی, 2016)
IntroductionThe main objective of the training, is the academic self- efficacy of the student as the next generation of society that their growth requires social support and academic motivation. students social support and motivation will cause socialÂ  and universal development.Self-efficacy is one of the most important elements of success and consistency in the field of positive psychology falls(Snyder&Lopez, 2002). self- efficacy is the student belief in his ability to Achieve goals in a specific academic field and perform a task successfully (Zimmerman, 2006, Schunk, 2008 and Dorman, 2010). These beliefs will influence of Â student thinking, feeling, motivation and behavior. Â A strong sense of self- efficacy improve positive personal views, participate in activities, set goals and work commitment(Strobel et all, 2011).Social support can be through providing the ground of activity, gain positive experience, sense of worth and stability in the social life will be a success(Karademas, 2006). Along with the social support, academic motivation also influence on educational activities,Â  and helps students achieve academic goals(Alaii kharaem et all, 2012). This study sought to examine the relationship between social support, academic motivation with academic self-efficacy to improve students educational and social achievements. Â Â Â Â Methods& Materials This research method was descriptive correlation. The study population included male and female students in all highschools in Tabriz and Azarshahr City is 90-91 on the year that their total number is 37347. Sample size based on Table Krejcie & Morgan (1970)and 278 subjects were selected by random cluster. Questionnaire was used be academic self-efficacy from Ralph Matthews Shvarzr Jerusalem (1981) and the Social Support Questionnaire Vaux, Phillips, Holley, Thompson, Williams & Stewart (1986) and academic motivation questionnaire Gholipoor fence and Bahrami(1994). According to experts, the questionnaire content validity and reliability with internal consistency estimate (Cronbach's alpha) for the self-efficacy questionnaire, 83/0 and the Social Support Questionnaire 84/0 and a motivation questionnaire, 0/93, respectively. For data analysis,descriptive statistics and Pearson correlation, regression, t-testwas used.Â Discussion of results and conclusionThe results showed that there is a significant relationship between social support and academic motivation with academic self-efficacy respectively, 0/38, 0/30. Regression analysis results showed that social support and academic motivation can predict academic self-efficacy(regression coefficient 0/20 and standard regression coefficient 0/450. The results showed that social support and academic motivation affects the academic self- efficacy. These findings are consistent with studies Solberg & Torres (2001) and Bandura's theory. Social support through punishment and reward the activities, can be impact on academic self-efficacy. Feedback and confidence that others provide individual academic ability can enhance a person's self-efficacy. The results showed a significant and positive correlation between academic motivation and academic self-efficacy and the academic motivation could predict 0/26 percent of variance academic self- efficacy. Many researchers believe that self-efficacy and academic achievement are related. According to research conducted by the Kabiri (2003) and Green et all (2004), self-efficacy can have an important role In predicting academic performance at different levels. Usher & Pajares (2006) also concluded that self- efficacy belifes has a full role in academic efficacy, learning and academic achievement.self-efficacy is the student belief about his ability to perform a variety of academic tasks. Students with high academic self- efficacycan do their academic tasks better than students with lower academic self-efficacy. The high level of academic self-efficacy, resulting in earn higher grades and are trying to do homework. Family, friends, and peers can affect a student academic self- efficacy because these groups supports, can lead students to certain about its capabilities.The findings showed that there is no significant difference in terms of academic self-efficacy betweenÂ  male and female students but this difference in the case of academic motivation was significant.In summing up the results of the study can say that, social support and academic motivationÂ  are the factors that influencing the increase or decrease in academic self-efficacy. These factors can lead to trust, high motivation, self-efficacy and effort and the success of the student to be followed.Â